(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Cloud computing has gained a lot of hype in the current world of I.T. Cloud computing is said to be the next big thing in the computer world after the internet. Cloud computing is the use of the Internet for the tasks performed on the computer and it is visualized as the nextgeneration architecture of IT Enterprise. The ‘Cloud’ represents the internet. Cloud computing is related to several technologies and the convergence of various technologies has emerged to be called cloud computing.Open source systems refer to software systems whose source code is available, allowing for immediate incorporation of improvements and adaptations of the system by its users. This seminar reports on an evaluation of open source management tools for cloud computing. Cloud computing is not a magical solution, planning and management of resources and the cloud in itself is pivotal. In this report, we compare and evaluate a number of open source tools used in the industry to manage and automate the cloud. We evaluate provisioning tools, orchestration tools, configuration tools and monitoring tools. Keyword: management of cloud with open source tools.